Large dams not for the poor - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Referring to the 'very well done' article on large dams in Spore 80, Guy Barthélemy of Villages sans Frontières in Salies de Bearn, France, corrects us: 'Your arguments lack conviction when it comes to the large-scale dams that are being planned...